Automatic License Plate Detection System with YOLOv11 Algorithm - Kurniawan, Nicholas Alfandhy; Sari, Christy Atika (Politeknik Negeri Batam, 2025)
The increasing number of motor vehicles in Indonesia demands technological solutions to enhance efficiency and security, particularly in automatic license plate recognition systems. This study aims to develop an automatic license plate detection system using the YOLOv11 algorithm to detect license plates and their characters in real-time. The research methodology includes collecting datasets from Kaggle, RoboFlow, and manual acquisition, followed by annotation, data augmentation, model training, and interface development using Tkinter and OpenCV. The dataset comprises 4000 license plate images and 3000 characters images, divided for training, validation, and testing. Evaluation results demonstrate strong model performance, with precision of 0.891, recall of 0.911, mAP50 of 0.906, and mAP50-95 of 0.631 for license plate detection, and precision of 0.889, recall of 0.912, mAP50 of 0.907, and mAP50-95 of 0.629 for character detection. Real-time testing showed that 12 out of 12 license plates were successfully recognized, influenced by lighting conditions, distance, and plate orientation. This study produced an efficient system for parking security, with potential for further development.